(untitled) (مجلة إحالات, 2025)
تميزت بلديّة سيدي خالد -الواقعة غربا في منطقة بسكرة-، بطابع ديني خاص، لاسيما وهي تحمل ضريحاً مشهوراً للرجل الصالح " خالد بن سنان العبسي"، هذا الأمر الذي أنشأ تصوّفا واضحا في معتقد أئمتها وعلمائها، ثم انتقل ذلك إلى شعرائها، لتخلق بتجاربهم الصوفية رؤية شعرية خاصة فتتجسّد في لغتهم الشعرية الصوفية، وهذا ما عالجته هذه الورقة البحثية. Abstract: Sidi khaled country was marked ,in fact, the West in logic of Biskra has a special religious character, especially as it occupies a famous mausoleum of the righteous man Khaled Ben Sinane El-Absi, This created a clear mysticism in the belief of its imams and scholars, and then it was passed on to its poets, to create their own mystical experiences of poetic version renewed in the language of poetic Sufi, and this paper .